2019
DOI: 10.3390/electronics8070729
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Renewable Energy Sources: The Role of Energy Storage in the European Power System of 2040

Abstract: Global electricity demand is constantly growing, making the utilization of solar and wind energy sources, which also reduces negative environmental effects, more and more important. These variable energy sources have an increasing role in the global energy mix, including generating capacity. Therefore, the need for energy storage in electricity networks is becoming increasingly important. This paper presents the challenges of European variable renewable energy integration in terms of the power capacity and ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
116
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(116 citation statements)
references
References 41 publications
0
116
0
Order By: Relevance
“…In addition, the results of analysis conducted by Norwood et al [37] indicate that solar thermal, PV, and battery ESS will play an important role in meeting Europe's targets for renewable energy supply. The results of the studies above have shown that ESS relieves the burden of the power system due to increased variable renewable energy integration by mitigating the volatility of the power generation output of renewable energy, including PV, and by providing the primary and secondary reserves for frequency regulation service [21][22][23]30,31,33,[35][36][37][38][39]. The studies also have verified that ESS increases the economic value of variable renewable energy by storing surplus power to participate in the energy trading market, and by bringing new investment opportunities through the substitution of a need to upgrade old distribution and substation facilities [32,34,39,40].…”
Section: Roles Of Ess To Integrate Pv Energymentioning
confidence: 99%
“…In addition, the results of analysis conducted by Norwood et al [37] indicate that solar thermal, PV, and battery ESS will play an important role in meeting Europe's targets for renewable energy supply. The results of the studies above have shown that ESS relieves the burden of the power system due to increased variable renewable energy integration by mitigating the volatility of the power generation output of renewable energy, including PV, and by providing the primary and secondary reserves for frequency regulation service [21][22][23]30,31,33,[35][36][37][38][39]. The studies also have verified that ESS increases the economic value of variable renewable energy by storing surplus power to participate in the energy trading market, and by bringing new investment opportunities through the substitution of a need to upgrade old distribution and substation facilities [32,34,39,40].…”
Section: Roles Of Ess To Integrate Pv Energymentioning
confidence: 99%
“…However, one drawback of renewable sources is their unpredictable nature and intermittency. To overcome this drawback, an attractive solution is to combine two or more energy sources in a hybrid system and include energy storage [3]. For example, photovoltaic power generation can be used during the day and wind power generation (which usually generates more energy) can be used at night, so the two sources of energy complement each other [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, electricity grids are designed considering energy sources that do not present variability, which happens with renewables, so electricity grids must have enough back-up capacity. Storage capacity is essential, thus making it possible to increase renewable generation while avoiding the possible problems that could be caused by its variability [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the problem of VRE sources integration with electric power systems is due to its intermittency; it is still a challenge for the grid operators when scheduling the power generation [6].…”
Section: Introductionmentioning
confidence: 99%